Comparative Performance Testing of the Impact of ACK Loss in TCP Tahoe, TCP Reno, and TCP New Reno on the ns-2 Simulator - Agung Hernawan (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
In TCP/IP networks, TCP provides reliable delivery service with the guarantee that packets sent reach their destination. This is achieved through the use of acknowledgments (ACK) as a mechanism. In TCP/IP networks, TCP provides reliable delivery service with the guarantee that packets sent reach their destination. This is achieved through the use of acknowledgments (ACK) as a mechanism. In all three variants of TCP, they rely on the presence of ACK packets. Therefore, testing will be conducted to observe the effect of ACK loss on TCP performance. The testing involves introducing disruptive traffic on the ACK path with varying magnitudes. This disruptive traffic results in the loss of some ACK packets, depending on the magnitude of the disruptive traffic. The testing was conducted using the ns-2 simulator software. The research findings indicate that the loss of ACK packets leads to a decrease in TCP performance. TCP Reno successfully improves the performance of TCP Tahoe, but the algorithm improvement in TCP New Reno does not have an effect on TCP Reno..